2014
DOI: 10.7326/m13-2796
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Antipsychotic Drugs and the Risk for Acute Kidney Injury and Other Adverse Outcomes in Older Adults

Abstract: Academic Medical Organization of Southwestern Ontario.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 125 publications
(108 citation statements)
references
References 31 publications
3
104
0
1
Order By: Relevance
“…These databases have been used extensively to research health outcomes and health services. [14][15][16][17][18][19][20] These databases were held securely in a linked, de-identified form at ICES and analyzed at the ICES Western site.…”
Section: Methods Study Designmentioning
confidence: 99%
“…These databases have been used extensively to research health outcomes and health services. [14][15][16][17][18][19][20] These databases were held securely in a linked, de-identified form at ICES and analyzed at the ICES Western site.…”
Section: Methods Study Designmentioning
confidence: 99%
“…However, our review identified two additional studies (Wang, 2011;Hwang et al, 2014) and pooled all risk estimates. Studies conducted before 2006 (Thorogood et al 1992, Penttinen and Valonen 1996, Pratt et al 1996, Enger et al 2004) were rated as low quality based on NOS scores.…”
Section: Discussionmentioning
confidence: 99%
“…AP use may merely be a marker for the presence of cardiovascular risk factors and not the reason for MI; alternately, APs may interact with state-dependent risk factors through unknown mechanisms to trigger MI. With regards to the non-significant elevation (Brauer et al, 2015;Pariente et al, 2012) in the risk of MI in long-term APs users, since the development of atherosclerotic plaque takes a period of years to decades, the mean follow-up time from participants in the analyzed cohort studies (approximately 6.5 years with the range of 1-13 years) (Enger et al, 2004;Hwang et al, 2014;Pariente et al, 2012;Pratt et al, 1996) may be insufficient for AP to meaningfully affect the MI process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations